Factors Affecting Students’ Performance in Speaking Class at English Department of Halu Oleo University - Annisa, Wa Ode Nur Awwaliyah; Kamaluddin, Kamaluddin; Nurnia, Nurnia (Universitas Halu Oleo, 2021)
Students' speaking performance can be affected by the factors that come from performance conditions (time pressure, planning), standard of performance and amount of support), affective factors (such as motivation, confidence, and anxiety), listening ability, topical knowledge, and feedback during speaking activities. The purpose of this study was to analyze, describe and determine factors affecting students' quality in speaking performance of the third semester of Halu Oleo University. This study employed a quantitative design. The data was collected by using a close-ended questionnaire. All the items questionnaire was analyzed by using SPSS version 20. The population was students of the third semester of Halu Oleo University in the academic year 2016/2017. The samples were 62 students of the English Department, which were taken by purposive sampling. The result of this research were factors affecting students' difficulties in speaking performance of the third-grade students of Halu Oleo University showed that from five factors namely affective factors, linguistic factors, performance condition, listening ability factors, and feedback during the speaking activities. The result found that, the dominant category or the high percentage on factors affecting students' difficulties in speaking performance was listening ability factors. Where listening ability factors included grammar, vocabulary, and pronunciation. It concluded that the students feel difficulty in speaking performance.